Production and Clinical Application of Keratobioimplants in Ukraine. Advances, Modern Challenges and Development Prospects - I. E. Aleshchenko; G. I. Drozhzhyna; V. V. Mikhailova; O. Yu. Babenko (Transplantation and artificial organs, 2021)
The article presents information on the current state of keratobioimplants production and clinical use in Ukraine. Thanks to the cooperation of the State Enterprise Bioimplant of the Ministry of Health of Ukraine with 13 ophthalmological institutions, keratobioimplants have been successfully used to treat corneal diseases since 2014. Over 7 years the enterprise has manufactured and provided for treatment 1799 keratobioimplants from the donor cornea of the human eye for various types of keratoplasty.The donors were analyzed by age, infection level, optimal timing of keratolimbal discs retrieval as well as morphometric parameters of endothelial cells.Long-term clinical outcomes demonstrate high quality of engraftment and steady increase in visual acuity in patients after penetrating keratoplasty. In 99.4% of the patients undergoing curative keratoplasty, the inflammatory process was stopped, the destruction of the cornea was stopped, and the eyes were preserved for further surgical ophthalmological interventions.